PERAN KELUARGA DALAM PENINGKATAN KEMAMPUAN INTERAKSI SOSIAL BERMASYARAKAT KLIEN SKIZOFRENIA PASCA PERAWATAN DI RUMAH SAKIT - Lailatul Maghfiroh; Khamida Khamida (Universitas Nahdlatul Ulama Surabaya, 2015)
Family has a strategic function for the schizophrenic client’s social interaction, the role of family really needs to reached client independent, The role of family enables the schizophrenic individual to re-adapt the social life in the society. This research destination to analyze realiontship the family role and the Scizophrenic client’s interaction level in the social life. This research applied the analytic cross sectional design. The populations of the research were the schizophrenic clients who have been hospitalized and left the RSJ Menur Surabaya (Surabaya Menur Mental Hospital) and their family who lived in Surabaya moreless 30 respondens with samples taken by using the total population method involved 28 repondents. For independent variable the family role anddependent variable is level interaction society. The data were collected by filling out the checklist, doing observations and interviews which were then analyzed by using the SPSS and the Rank Spearman statistical test with the significance level p < 0,05. The result of the research showed that the family role contributed the family role was shown by 12 respondents (42,8%). The schizophrenic clients social interaction level sufficiently was shown by 14 respondents (50%). The statiscal test revealed the result that p < 0,05 = 0,10 < 0,05 so that Ho was can’t accepted. This research concluded that there was a relationship between the family role and the schizophrenic clients social interaction level in the social life posttreatment in RSJ Menur Surabaya. So that, the staff of hospital give role every room at RSJ Menur Surabaya (Surabaya Menur Mental Hospital) the family need to direct follow for Schizoprenic client’s in cure at RSJ Menur and for nurse advice to family give maximal attention.